Probiotics improve symptoms of patients with COVID-19 through gut-lung axis: a systematic review and meta-analysis - Tian, Yong; Ran, Hongmei; Wen, Xudong; Fu, Guochuan; Zhou, Xiaofang; Liu, Rui; Pan, Tao (Frontiers in Nutrition, 2023)
Background: Multi system symptoms such as gastrointestinal tract and respiratory tract exist in coronavirus disease 2019 (COVID-19) patients. There is a lack of high-quality evidence to prove that probiotics are effective in improving these symptoms. In this study, we aimed to evaluate the efficacy of probiotics in meta-analysis. Methods: We systematically searched PubMed, Embase, Web of Science, and Cochrane Library up to February 15, 2023. Randomized controlled trials or retrospective studies comparing the efficacy of probiotics with placebo in improving symptoms for patients with COVID-19 were included. This meta-analysis assessed endpoints using Review Manager 5.3. Result: Ten citations comprising 1198 patients with COVID-19 were included. The results showed that probiotics could increase the number of people with overall symptom improvement (RR=1.62, 95%CI[1.10, 2.38], P=0.01) and shorten the duration of overall symptoms (MD=-1.26, 95%CI[-2.36, -0.16], P=0.02). For specific symptoms, probiotics could improve diarrhea (MD=-2.12, 95%CI[-2.41, -1.83], P<0.00001), cough (MD=-2.21, 95%CI[-4.56, 0.13], P=0.06) and shortness of breath (MD=-1.37, 95%CI[-2.22, -0.53], P=0.001). Probiotics had no obvious effect on fever, headache and weakness. For inflammation, probiotics could effectively reduce C-reactive Protein (CRP) serum level (MD=-4.03, 95%CI[-5.12, -2.93], P<0.00001). Regarding hospital stay, probiotics group was shorter than placebo group (MD=-0.98, 95%CI[-1.95, -0.01], P=0.05). Conclusion: probiotics can improve the overall symptoms, inflammatory reaction and shorten hospital stay of patients with COVID-19. Probiotics may improve gastrointestinal symptoms (such as improving intestinal flora and reducing the duration of diarrhea) and further improve respiratory symptoms through the gut-lung axis.